Clinical and Basic Aspects of Neurofibromatosis Type 1 2022
DOI: 10.5772/intechopen.98661
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Features of Neurofibromatosis Type 1-Associated Tumors

Abstract: Rewiring cellular metabolism is a key hallmark of cancer. Multiple evidences show that alterations in various metabolic circuits directly contribute to the tumorigenic process at different levels (e.g. cancer initiation, metastasis, resistance). However, the characterization of the metabolic profile of Neurofibromatosis type 1 (NF1)-related neoplastic cells has been only partially elucidated both in benign neurofibromas and in malignant peripheral nerve sheath tumors (MPNSTs). Here, we illustrate the state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Observations indicate that affected individuals tend to present with deviations in their metabolic profiles, which may contribute to their smaller size and stature. Additional studies have revealed a lower prevalence of diabetes mellitus (mainly type 2) among NF1 patients, suggesting a complex interplay with signals and molecular pathways involved in glucose homeostasis and insulin signaling [151]. In fact, reduced thalamic glucose metabolism could be related to cognitive impairments [152].…”
Section: Stature and Metabolic Homeostasis Dysregulationmentioning
confidence: 99%
“…Observations indicate that affected individuals tend to present with deviations in their metabolic profiles, which may contribute to their smaller size and stature. Additional studies have revealed a lower prevalence of diabetes mellitus (mainly type 2) among NF1 patients, suggesting a complex interplay with signals and molecular pathways involved in glucose homeostasis and insulin signaling [151]. In fact, reduced thalamic glucose metabolism could be related to cognitive impairments [152].…”
Section: Stature and Metabolic Homeostasis Dysregulationmentioning
confidence: 99%